The Influence of Innovation on the Performance of Small and Medium Manufacturing Enterprises in Tanzania - NG`WASA, Ndahani; CHACHAGE, Bukaza; KARA, Nasra (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This study examines the role of innovation in enhancing the performance of manufacturing SMEs in Tanzania, focusing on the influence of product and process innovation on market innovation and overall firm performance. As innovation becomes crucial for competitiveness, particularly in resource-constrained developing economies, this research positions it as an essential element for SMEs to adapt, differentiate, and thrive in dynamic markets. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data from 277 SME owners and managers, the study reveals that both product and process innovation significantly boost market innovation, which in turn positively impacts firm performance. These findings suggest that market innovation enhances a firm's adaptability, customer engagement, and competitive edge. The study offers empirical insights into the role of multidimensional innovation in supporting SME growth within a developing economy, emphasizing that incremental changes alone may not sustain a competitive advantage. The results underscore the importance of strategic investment in innovation capabilities across product, process, and market domains. For policymakers and SME support institutions, the study calls for initiatives that improve access to resources, training, and technology to facilitate innovation. By highlighting the link between innovation and firm performance, this research reinforces innovation as a cornerstone for sustainable SME growth, demonstrating that a comprehensive innovation strategy enables SMEs to overcome market challenges, deliver value, and achieve long-term success.